Artificial intelligence in anti-dengue drug development - Roney, Miah (Elsevier, 2024)
Dengue fever is a mosquito-borne illness that affects millions of people worldwide. Artificial intelligence (AI) is being employed in the battle against it. AI is being used to analyse dengue immune repertoires, which may yield hitherto unheard-of insights into the complexities of dengue adaptive immunity, help in the development of novel treatments, and influence the creation of vaccines. This AI-driven strategy may contribute to the creation of dengue fever therapies that are more potent.